Star Clusters in the Era of Large Surveys: Proceedings of Symposium 5 of JENAM 2010 - Moitinho, André; Alves, João (Springer-Verlag Berlin Heidelberg, 2012)
The symposium "Star Clusters in the Era of Large Surveys" was held in Lisbon on Sep 9-10 during the JENAM 2010. It served as a platform for discussing what and how recent, on-going and planned large-area ground-based and space-based surveys can contribute to producing a major leap in this research field, which has a strong European history. Scientific topics addressed included: cluster searches, clustered vs. isolated star formation, large-scale star formation, enrichment of the field population, structure, populations and evolution of the Milky Way, cluster dynamics (internal and within the M
Description based upon print version of record
Keywords: Konferenzschrift; Konferenzschrift -- Lissabon 2010; Sternhaufen